MENYELAMI IDENTITAS LOKAL DAN TANGGUNG JAWAB SPIRITUAL PADA MASJID SYEKH YUSUF DI KABUPATEN GOWA - Jusmiati; Syamzan Syukur; Umar Sulaiman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
This research explores how to explore the local identity and spiritual responsibility of the people in Gowa Regency at the Syekh Yusuf Mosque. This research uses field research with historical, religious, and sociological approaches. The data collection methods used were observation, interviews, documentation, and literature. Data processing and analysis techniques are data reduction, data presentation, and conclusions. The results of this research show that the existence of the Sheikh Yusuf Grand Mosque is an embodiment of culture and the center of Muslim activities in the Gowa Regency. This realization can be explored using stages that are structured and sustainable. One of the stages in question is the public's understanding of the architectural morphology of buildings. The architectural morphology of the Syekh Yusuf Grand Mosque building has a very unique design while still combining Islamic concepts, history, and local cultures such as the sulapa' eppa' motif which is the philosophy of life of the Bugis-Makassar tribe which depicts the human character and nature, namely, wind, fire, water, and land. Humans who can balance these four characteristics are called humans who have Siri' and Pesse' which are strongly held by the Bugis-Makassar tribal people. From this combination, the Sheikh Yusuf Mosque does not abandon its function as a building of worship for the people to improve spirituality in the context of a relationship with Allah SWT. and relationships with fellow humans in presenting the breath of Islam in every aspect of people's lives as a filter for the flow of globalization.